Functional and structural characterization of AntR, an Sb(III) responsive transcriptional repressor. Issue 2 (16th April 2021) - Viswanathan, Thiruselvam; Chen, Jian; Wu, Minghan; An, Lijin; Kandavelu, Palani; Sankaran, Banumathi; Radhakrishnan, Manohar; Li, Mingshun; Rosen, Barry P.
Abstract: The ant operon of the antimony‐mining bacterium Comamonas testosterone JL40 confers resistance to Sb(III). The operon is transcriptionally regulated by the product of the first gene in the operon, antR . AntR is a member of ArsR/SmtB family of metal/metalloid‐responsive repressors resistance. We purified and characterized C. testosterone AntR and demonstrated that it responds to metalloids in the order Sb(III) = methylarsenite (MAs(III) >> As(III)). The protein was crystallized, and the structure was solved at 2.1 Å resolution. The homodimeric structure of AntR adopts a classical ArsR/SmtB topology architecture. The protein has five cysteine residues, of which Cys103a from one monomer and Cys113b from the other monomer, are proposed to form one Sb(III) binding site, and Cys113a and Cys103b forming a second binding site. This is the first report of the structure and binding properties of a transcriptional repressor with high selectivity for environmental antimony. Abstract : Antimony is an environmental toxic element associated with cancer, liver, cardiovascular and respiratory diseases. The ant operon of Comamonas testosterone JL40 isolated in an antimony mine confers resistance to antimonite. The operon is regulated by the AntR antimonite‐responsive transcriptional repressor. AntR responds to metalloids in the order antimonite = methylarsenite >> arsenite. A potential antimonite binding site is visible in the x‐ray crystal structure of AntR.